2001
DOI: 10.1063/1.1406936
|View full text |Cite
|
Sign up to set email alerts
|

Internal waves generated by the wake of Gaussian hills

Abstract: International audienceDepending on their structure and dynamics, the wakes of various obstacles can generate different kinds of internal waves in stratified fluids. Experiments on waves emitted by three-dimensional Gaussian models towed uniformly in a linearly stratified fluid were carried out. Beyond a critical value Frc of the Froude number Fr, the developed wake was observed to radiate an internal wave field shorter than the lee waves of the hill. The emergence of such waves is correlated with the periodic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Experimental papers report on good agreement with the linear predictions Eqs. (4) and (5) without significant influence from the object shape (Baines, 1979;Castro et al, 1983;Boyer and Tao, 1987;Kadri et al, 1996;Dupont et al, 2001). Note, however, that the dimensionless towing velocity in these experiments was restricted in the interval U/Nh ∈ [0.1, 0.8], which is much closer to an assumed linear regime than in our experiments.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Experimental papers report on good agreement with the linear predictions Eqs. (4) and (5) without significant influence from the object shape (Baines, 1979;Castro et al, 1983;Boyer and Tao, 1987;Kadri et al, 1996;Dupont et al, 2001). Note, however, that the dimensionless towing velocity in these experiments was restricted in the interval U/Nh ∈ [0.1, 0.8], which is much closer to an assumed linear regime than in our experiments.…”
Section: Discussionmentioning
confidence: 48%
“…Most of the data seem to collapse onto a line of slope ∼1/2, outliers are the results for obstacle "B" towed with the gentle slope leeward. Note that Dupont et al (2001) found in their experiments the same linear relationship c gz = mU, even the constant of proportionality m was found to be close to one-half.…”
Section: Initial Transientsmentioning
confidence: 68%
“…Body-forced lee waves are present in all situations but tend to be the dominant IW source at low Fr. At higher Fr, turbulent wake-generated IWs dominate (Dupont et al 2001). In this regime, the turbulent eddies within the wake will result in the generation of IWs.…”
Section: Stratified Wakesmentioning
confidence: 95%
“…Also relevant are the related studies of lee wave flows over topographic obstacles (i.e. objects mounted on a fixed surface) (Castro, Snyder & Baines 1990;Vosper et al 1999;Dupont et al 2001;Dalziel et al 2011). Although many of these studies are at low Re, they exhibit the same wavefield features as objects towed in an unbounded flow.…”
mentioning
confidence: 97%
“…One might be tempted to correlateλ H to the size of quasi-two-dimensional coherent structures within the wake, e.g. see Dupont, Kadri & Chomaz (2001). It is known that the Strouhal number St = D/λ x scales as (X/D) −1/3 , where λ x is the horizontal length scale of the coherent structures.…”
Section: Wave Selection Mechanismmentioning
confidence: 99%